Water-soluble N-heterocyclic carbene platinum(0) complexes: Recyclable catalysts for the hydrosilylation of alkynes in water at room temperature - Silbestri, Gustavo Fabián (2012)
The synthesis and characterization of new water-soluble platinum(0) complexes bearing sulfonated N-heterocyclic carbene (NHC) and divinyltetramethylsiloxane (dvtms) ligands are described. These complexes, of the general formula (NHC)Pt(dvtms), are active and recyclable catalysts for the hydrosilylation of phenylacetylene and other alkynes at room temperature in water. Our findings indicate that the NHC-Pt(0) bonds are reasonably stable under these catalytic conditions, although hydrolysis is observed at temperatures above 80 °C in pure water. © 2012 American Chemical Society.